The immune response to a two-dose schedule of quadrivalent HPV vaccine in 9–13 year-old girls: Is it influenced by age, menarche status or body mass index?. Issue 49 (20th November 2019) - Sauvageau, Chantal; Gilca, Vladimir; Donken, Robine; Fan, Shu Yu; Ogilvie, Gina; Dobson, Simon
Abstract: HPV vaccines are highly immunogenic. A two-dose schedule for 9–14 year-old is recommended. However, no data exist regarding the impact of age, menarche status and body mass index (BMI) on the immune response to a two-dose schedule. In this post-hoc analysis, we present antibody titers to HPV6/11/16/18 in 9–13 year-old girls participating in a randomized clinical trial and assigned to receive two doses of quadrivalent HPV vaccine at 6 months interval (NCT00501137). Antibody titers were measured at month 7 and 24 of the study by using a competitive Luminex immunoassay (cLIA). Both, at Month 7 and 24 the GMTs for four HPV genotypes were similar across the age bands, and did not vary significantly by menarche status. Overweight and obese girls had lower GMTs. More than 99% of girls remained seropositive for HPV 6/11/16 and 89% for HPV18 at month 24. Comprehensive data in overweight and obese vaccines are warranted.